Corrosion Behavior of Spray Pyrolysis–Deposited BaTiO₃, SiO₂, and BaTiO₃/SiO₂ Composite Coatings on Ti–13Nb–13Zr Alloy for dental implants - Hamzah K. Rustam; Shanai M. Al-Bayati (American Journal of Biology and Natural Sciences, 2026)
The long-term success of metallic implants depends on both corrosion resistance in physiological environments and strong osseointegration at the bone–implant interfaceIn, in this study Ti–13Nb–13Zr substrates were functionalized with BaTiO₃, SiO₂, and BaTiO₃–SiO₂ composite coatings deposited by spray pyrolysis. The rationale was to combine the piezoelectric stimulation of BaTiO₃ with the bioactive and surface-modifying properties of SiO₂ to achieve synergistic improvements in implant performance. Coatings were systematically optimized and characterized using XRD, EDX, FESEM test, and corrosion tests. The electrochemical corrosion test also achieved by measuring OCP, polarization curve tafel and EIS. Electrochemical tests revealed significantly lower corrosion current densities with higher polarization resistance for coated samples compared to the bare alloy, the BaTiO₃–SiO₂ composite showing the most stable electrochemical response. These findings indicate that spray-pyrolysed BaTiO₃–SiO₂ coatings provide a promising strategy to engineer multifunctional implant surfaces with superior corrosion protection and biological integration, advancing the design of next-generation load-bearing biomedical implants.in addition The result proves that the mixing between the two bioceramic combined the advantages of them and decreases the corrosion rate about 23 times; raise the protection efficiency to about 95%.